GORAN & HERRIC A Comparative Study of Two of Their Poems: "To the Ivy Flower" & "To Daffoils". - Muhiadeen, Galawezh Ibraheem (Sulaimani Journal for Pure and Applied Sciences, 1997)
Goran Abdullah Beg Sulaiman Abdullah Beg, comes from an important and educated family. His father and grandfather were both poets and also wrote on literature. Goran was born in 1904 in Halabja Province, Sulaimany governorate, Kurdistan of Iraq. He attended the primary school in Halabja andd Teachers' Training Institute in Kirkuk. He became a primary school teacher in 1937, and worked as a teacher in the villages of Halabja. In 1937, he left teaching and became director for the NEAR EAST RADIO BROADCASTING in Java, Palestine. In 1960, he became a lecturer in Baghdad University, College of Arts, Kurdish Department. He Died in 1962.